Understanding injection-induced seismicity in enhanced geothermal systems: from the coupled thermo-hydro-mechanical-chemical process to anthropogenic earthquake prediction - Rathnaweera, Tharaka Dilanka (2022)
Injection-induced seismicity has become a major barrier to the development of geothermal energy, because the complexity of fault behaviors and the lack of physical fundamentals make it extremely difficult to assess, predict, and control during geothermal energy extraction. The motivations of this review include, (1) to identify the recent advances in understanding and modelling of coupled thermo-hydro-mechanical-chemical (THMC) processes in enhanced geothermal systems (EGS), and (2) to apply the THMC processes for improving our ability to predict the occurrence of the anthropogenic earthquakes. Fault activation is associated with several processes, including pore pressure diffusion, temperature alteration and stress-aided corrosion, and can be simulated by pore-scale modelling. However, there is still a rudimentary understanding of how these processes fit together with the spatial and temporal distribution of the induced earthquakes. Uncertainty in the seismic moment prediction, such as the interaction between the reservoir operations and fault responses, hinders the development of EGS. The current challenges in the earthquake prediction include the quantification of stress state, complexity of reservoir structure, and proper strategy of fluid injection. Cyclic soft stimulation and borehole seismometer feedback have been successfully used to mitigate the risks associated with fluid injection. Nevertheless, in some circumstances, the activation of nearby blind, critically stressed faults is uncontrollable, no matter how much fluid is injected into the reservoir.